Immunohistochemical evaluation of cellular composition of the immune system of lymph nodes in acute appendicitis (Journal of Medical Science, 2019)
Introduction. There is not much data about the composition of populations of the immune system in acute appendicitis. The basic histopathological criterion for the diagnosis of acute appendicitis is neutrophil infiltration of the muscle membrane. Aim. The subject of this publication is a semi-quantitative evaluation of B lymphocytes (CD20+), T lymphocytes (CD3+) and macrophages (CD68+), and the determination of the number of active lymph nodes during the course of inflammation. Material and Methods. The study material was obtained from 79 patients who had an appendectomy due to acute appendicitis. In this group, the tissue was obtained from: 34 women (aged 20 to 91) and 45 men (aged 20 to 72). Results. In the course of acute appendicitis, there is involvement of lymph node B lymphocytes, T lymphocytes and macrophages. Independent of the type of inflammation, the cellular make-up of the nodes is similar. The number of lymph nodes decreases with age and is gender dependent. Conclusions. In the course of acute appendicitis, there is involvement of lymph node B lymphocytes, T lymphocytes and macrophages. The number of lymph nodes decreases with age and is gender dependent. A statistically significant number of the examined cells of the immunological system in the lymph nodes changed due to inflammation (p<0.001). B and T lymphocytes in the lymph nodes and in the mucous membrane of the appendix differed depending on the sex, and the presence of B lymphocytes in the mucous membrane was significantly higher in the group of 20-40 years of age. T lymphocytes were predominant in the centres of the lymph nodes in groups 20-40 and 61-91 years of age, and in the peripheral zones in the group of 41-60 years of age.